Study on mineralogy and chemistry of the saprolitic nickel ores from Soroako, Sulawesi, Indonesia: Implication for the lateritic ore processing - Sufriadin Sufriadin; Arifudin Idrus; Subagyo Pramumijoyo; I Wayan Warmada; Akira Imai (Geological Engineering Department Universitas Gadjah Mada, 2015)
An investigation of mineralogy and chemistry of saprolitic nickel ores developed on ultramafic rock with different serpentinization degree from Soroako, Sulawesi has been conducted using X ray diffraction, thermal analysis, FTIR, and ICP-AES. The implication for the processing of these ores under acidic media was also studied. Weathering of unserpentinized peridotite in the Soroako west block produces saprolitic ore containing minerals such as relict olivine, goethite, quartz, talc with minor serpentine and smectite; whereas the weathered materials overlaying serpentinized peridotite in the Petea area are mainly composed of residual serpentine with lesser chlorite, maghemite, and remnant pyroxene and amphibole. Chemical analysis determined by ICP-AES demonstrates that west ore is higher in Si, Mg, and Ni, as compared to that Petea ore. Conversely, Fe and Al concentrations are higher in Petea ore than in west block ore. SEM-EDX examination reveals that olivine, talc, serpentine and goethite are the Ni-bearing phases occurring in west block ore; while serpentine is the principal host for Ni in the Petea ore. Chemical leaching under sulfuric acid reveals that olivine has highest dissolution rate in the west ore followed by serpentine; while talc, pyroxene, and iron oxides have slow dissolution rates. In contrast, serpentine in Petea ore is easily dissolved and is followed by chlorite; whereas amphibole, pyroxene, and maghemite are difficult to leach. Quartz is present in both ores and it seems to be undissolved during the chemical leaching. It is shown that Ni recovery from Petea saprolitic ore is higher than that of West Block ore.